Arabic Language Variation: Azharian Students' Perspectives on Fushhâ and ‘Âmmiyah - Kadar, Haerani; Nasiruddin, Nasiruddin; Pratama, Budi; Yusri, Islam (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
The targets of this studies is to analyze the barriers to the usage of fushhâ Arabic and the usage of ‘âmmiyah as a verbal exchange language by using Al-Azhar Cairo students. This research makes use of a qualitative approach with a case have a look at technique aimed at exploring the boundaries confronted with the aid of Al-Azhar Cairo students, especially foreign students from Indonesia, in using fushhâ and ‘âmmiyah Arabic simultaneously. information changed into collected through in-intensity interviews with 10 college students from numerous faculties and observations. The research results revealed several linguistic obstacles such as differences in sound system, vocabulary and grammar between fushhâ and ‘âmmiyah Arabic. Apart from that, non-linguistic obstacles were found such as a lack of language environment (bî'ah al-lughawiyah) and minimal access to fushhâ Arabic learning resources. Another obstacle is the significant differences in dialect, vocabulary and grammar of ‘âmmiyah Arabic and fushhâ Arabic. The implication of this research is that it theoretically contributes to the theory about obstacles in studying fushhâ and ‘âmmiyah Arabic simultaneously. Strengthening the theory about the significant differences between fushhâ and ‘âmmiyah Arabic from a linguistic and non-linguistic perspective. Meanwhile, practically for educational institutions, it can be an input in developing a more effective curriculum, teaching methods and learning environment. For teachers, it provides insight into students' obstacles, so they can design more accommodating teaching strategies. For the government, it can be a consideration for developing more effective Arabic language learning support programs.